Steppe complex of the middle part of the Egorlyk valley (Stavropol Upland) - Belous, V. N. (Проблемы ботаники Южной Сибири и Монголии, 2020)
The article highlights the current state of plant communities in the steppe complex of Middle Yegorlyk.The patterns of distribution of grass communities depending on the area’s landscape-environmental features are shown.The main formations of dry (real), hemigalophytic and grass-cereal phytocenoses and their edaphic variants are indicated.The species of floristic nucleus of representative communities are given. The originality and regional features of thestudied steppes are associated with their border position in the contact zone of the eastern Black Sea plains steppes andthe Stavropol Upland.